Investigating the Effect of Cement and Fibers Containing Fatty Arbocell on the Mechanical and Moisture Properties of Cold Emulsion Asphalt Mixtures - Alireza Motamadnia; Hamid Shirmohammadi; Morteza Asadamregi (پژوهش‌های زیرساخت‌های عمرانی, 2023)
Cold emulsion asphalts have advantages and disadvantages. The advantages of this type of mixture are related to the low temperature of production, environmental considerations, and its portability to long distances. One of the main reasons for the poor performance of this type of asphalt is its moisture content. The water penetration hinders the fracture of emulsion bitumen, and after that, the mixture's resistance to moisture is reduced. The present research used the modified Marshall method to determine the optimal bitumen percentage. For this reason, one to three percent by weight of the asphalt-cement mixture and 0.3 to 0.5 percent by weight of fiber mixture containing fatty arbocell were added. The resulting samples were subjected to the Marshall strength, Marshall index modified Lottman and Nicholson tests. Based on the results, the Marshall strength was 47.88%, the Marshall index was 139%, adhesion was 41%, the ratio of indirect tensile strength was 21%, and the fluidity was 36.47%. According to the data obtained from this research, it is suggested that 3% cement and 0.3% fatty arbocell fibers should apply in cold asphalt mixtures.